Perception of Medical Students towards Studying Neurosurgery in Kenya: A Mixed Methods Study - Ojakapeli, Ben; Seltzer, Laurel; Karani, Mercy G.N.; Emojong, Ednah Brook; Matata, Kavulavu Briton; Chaina, Brian; Samoe, Noah; Jebet, Chenger June; Nyambega, Silas; Limo, Ian Kipkorir; Oluoch, George Bryan Omondi; Nambiro, Angela; Lotodo, Teresa; Ayumba, Barry; Radwanski, Ryan (WFNS Journal, 2025)
Neurosurgery, a highly demanding and vital medical specialty, faces significant challenges in sub-Saharan Africa, where a shortage of trained neurosurgeons persists. This study aimed to explore the perceptions of medical students in Kenya regarding neurosurgery as a career choice.This is a cross-sectional study. A questionnaire was administered to collect both quantitative and qualitative data. It was pretested for clarity and validity, and included questions on demographics, interest in neurosurgery, confidence, exposure to neurosurgery during medical education, and faculty support experience. Quantitative data were analyzed using the chi-square tests, Kruskal–Wallis tests, and ordinal regression. Qualitative responses consisted of open-ended questions and were assessed using thematic analysis.The survey was distributed to 324 students, and 225 responses (69.4%) were received. Among respondents, 54.2% expressed interest in neurosurgery. Confidence in pursuing neurosurgery was found to be a strong predictor of interest. Key challenges reported were a lack of mentorship (60.9%), insufficient clinical exposure (39.1%), and limited faculty support (60.9%). Thematic analysis of qualitative responses highlighted the need for enhanced mentorship programs, increased clinical exposure, structured educational resources, and better work–life balance support.The findings, while limited, begin to underscore the importance of improving mentorship, clinical exposure, and structural support for medical students in sub-Saharan Africa. Addressing the deficit of the available neurosurgical workforce in Kenya begins with addressing the deficit in student development. This study offers insights from current medical students in Kenya on the barriers preventing their pursuit of neurosurgical training. These findings may also be relevant to other Low-and Middle-Income Countries (LMICs) with similar challenges.
Keywords: career perception; neurosurgery; mentorship; medical students; Kenya; sub-Saharan Africa; LMICs